Combination of Chest Physiotherapy and Postural Drainage for Airway Clearance in Bronchopneumonia: A Case Study - Alfarizi, Muhammad; Juliningrum, Peni Perdani; Sulistyorini, Lantin; Primirti, Irmarawati Dia (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
Background: Respiratory diseases such as bronchopneumonia contribute to the highest cause of death in children aged less than two years. Airway clearance becomes a problem due to the accumulation of secretions, resulting in airway obstruction. Independent nursing interventions such as chest physiotherapy can be carried out to free the airway and reduce the burden of breathing. Objective: This study aimed to analyze the application of chest physiotherapy intervention in bronchopneumonia children with airway clearance problems. Method: The research design uses a case study with a nursing process approach. The sample for this study was one child patient aged nine months with bronchopneumonia who was taken using a convenience sampling technique. Data was collected using interviews, observation, and documentation studies using pediatric nursing care format instruments. Chest physiotherapy intervention was carried out three times with a duration of 10-15 minutes with a combination of postural drainage, which was then evaluated before and after the procedure. Results: Chest physiotherapy intervention in patients can improve coughing ability, increase sputum production and respiratory rate 40 times per minute, and decrease rhonchi and oxygen saturation by 96%. Conclusion: Chest physiotherapy can be an effective independent nursing intervention to overcome the problem of ineffective airway clearance nursing in children with bronchopneumonia.